Item Response Patterns on the Patient Health Questionnaire-8 in a Nationally Representative Sample of US Adults - Tomitaka, Shinichiro; Kawasaki, Yohei; Ide, Kazuki; Akutagawa, Maiko; Yamada, Hiroshi; Yutaka, Ono; Furukawa, Toshiaki A. (Frontiers in Psychiatry, 2017)
Recent studies have shown that item responses on the Center for Epidemiologic Studies Depression Scale (CES-D) and Kessler Screening Scale for Psychological Distress (K6) exhibit the same characteristic item response patterns among the general population. However, the distributional patterns of responses on the Patient Health Questionnaire-8 (PHQ-8) among the general population have not been adequately studied. Thus, we conducted a pattern analysis of PHQ-8 item responses among US adults. Data (18,446 individuals) were obtained from the 2015 Behavioral Risk Factor Surveillance Survey (BRFSS). Item responses on the BRFSS version of the PHQ-8 were scored using the number of days response set and then converted to the original 4-point scale. The patterns of item responses were analyzed through graphical analysis. Lines of item responses scored using the number of days response set showed the same pattern among the eight items, characterized by crossing at a single point between “0 days” and “1 day,” and parallel fluctuation from “1 day” to “14 days” on a semi-logarithmic scale. Lines of item responses converted to the 4-point scale also showed the same characteristic pattern among the eight items. The present results demonstrate that the item responses on the PHQ-8 show the same characteristic patterns among items, consistent with the CES-D and the K6.